ChemInform Abstract: Diastereoselective Ruthenium Porphyrin‐Catalyzed Tandem Nitrone Formation/1, 3‐Dipolar Cycloaddition for Isoxazolidines. Synthesis, in silico Docking Study and in vitro Biological Activities. Issue 19 (18th April 2013) - Reddy, Annapureddy Rajasekar; Guo, Zhen; Siu, Fung‐Ming; Lok, Chun‐Nam; Liu, Fuli; Yeung, Kai‐Chung; Zhou, Cong‐Ying; Che, Chi‐Ming
Abstract The described method features a broad scope of alkene compounds, excellent compatibility of various functionalities, neutral reaction conditions, and high regio‐, chemo‐ and diastereoselectivity.